"My Worker Was There When it Really Mattered": Foster Care Youths' Perceptions and Experiences of Their Relationships with Child Welfare Workers. Issue 4 (October 2015) - Augsberger, Astraea; Swenson, Emilie
The study examines foster care youths' perceptions of their relationships with child welfare caseworkers, including the characteristics youth value and the supports they seek surrounding decision making while in foster care. Interviews were conducted with 18 foster care youth. Qualitative analysis identified perceived trust as an overarching theme connecting three subthemes: worker continuity, worker nonjudgmental listening, and worker ability/willingness to transcend the confines of the role. Workers should receive specialized training so they can better understand the developmental stages of adolescence and emerging adulthood, view these youth in the context of the youths' life experiences, and refine their interpersonal skills to better respond to the needs of this age group. Policy and program efforts should focus on reducing workforce turnover.